STUDY OF THE GENERATION GAP BETWEEN GIRL STUDENTS AND THEIR PARENTS - Anil Prasad (International Journal of Multidisciplinary Research and Studies, 2021)
Childhood relationships build a person's identity because they inspire or reject family members who serve as role models, which shapes feelings and behaviours (Brannen et al., 2004). Children's lives are shaped by the frequency and intensity of interactions among family members as well as the kind of family structure. Falk and Falk (2005) provided six hypothetical categories of family configurations in which kids may grow up. The first of them is autocratic, when children are not permitted to express their opinions, participate in decision-making, or take the initiative. The second type of structure is authoritarian, where children are free to voice their thoughts and opinions but only their parents are authorised to make choices. Third-ranked democratic structures give kids some control over their conduct, yet the ultimate choice still needs parental approval. The voices of children are given the same weight by an egalitarian system as the words of their parents. Contrarily, a permissive framework provides people more autonomy over their own lives than their parents do. Last but not least, the Leissez Faire structure forbids complete parental engagement in children's issues. All children are in their decisions.